A screening protocol incorporating brain-computer interface feature matching considerations for augmentative and alternative communication. Issue 3 (3rd May 2020) - Pitt, Kevin; Brumberg, Jonathan
ABSTRACT: Purpose : The use of standardized screening protocols may inform brain-computer interface (BCI) research procedures to help maximize BCI performance outcomes and provide foundational information for clinical translation. Therefore, in this study we developed and evaluated a new BCI screening protocol incorporating cognitive, sensory, motor and motor imagery tasks. Methods : Following development, BCI screener outcomes were compared to the Amyotrophic Lateral Sclerosis Cognitive Behavioral Screen (ALS-CBS), and ALS Functional Rating Scale (ALS-FRS) for twelve individuals with a neuromotor disorder. Results : Scores on the cognitive portion of the BCI screener demonstrated limited variability, indicating all participants possessed core BCI-related skills. When compared to the ALS-CBS, the BCI screener was able to modestly discriminate possible cognitive difficulties that are likely to influence BCI performance. In addition, correlations between the motor imagery section of the screener and ALS-CBS and ALS-FRS were non-significant, suggesting the BCI screener may provide information not captured on other assessment tools. Additional differences were found between motor imagery tasks, with greater self-ratings on first-person explicit imagery of familiar tasks compared to unfamiliar/generic BCI tasks. Conclusion : The BCI screener captures factors likely relevant for BCI, which has value for guiding person-centered BCI assessment across different devices to help inform BCI trials.